Development of model toward predictive analytics use to guide tactical non-clinical decision making in Qatar hospitals - Mohamed Mahmoud, Fatimetou Zahra; Mohamadali, Noor Azizah (Center for Promoting Ideas (CPI), USA., 2021)
Healthcare predictive systems are analytic systems which aim to minimize the future medical cost and help to provide in hospital a high level of healthcare and preventive healthcare due to the early detection of risks and possibility to take better actions and decisions. Recently, predictive analytics have acquired a wide spread among organizations from different sectors and purposes of use such in education, in governmental organization, in supply chain, public transportation, IT service providers and others to improve services, minimize costs, reduce time, retaining customers, and wining a business advantage. In healthcare sector organizations have start using predictive analytics to discover trends, patterns and predictions that help in improving the healthcare services. Even so, these efforts in healthcare sector still immature in comparison to the use of predictive analytics and its success in other sectors. This research studies the relationship between the use of predictive analytic systems and the tactical non-clinical decision-making performance in Qatar hospitals. The research model was developed on the basis of the unified theory of acceptance and use of technology (UTAUT) and the motivational framework for understanding information system use and decision performance. A Questionnaire has been developed to collect data through from various hospitals by focusing on information technology staff and managers, health information systems professionals and managers, administration staff and middle managers. The empirical findings will be published after analyzing the data and getting the results of the analysis